Bertahan di Tengah Krisis: Kesinambungan Pabrik Gula Kebon Agung di Malang 1930an - 1958 - Dwi Meya, Ramadhani; La Ode, Rabani (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
This study discusses the continuity of the Kebon Agung Sugar Factory from the crisis period in 1930 until it was nationalized in 1960. The economic crisis that hit Europe and the world had an impact on the collapse of most of the sugar industries in the Dutch East Indies. Kebun Agung Sugar Factory managed to survive in the midst of a global crisis that began towards the end of 1929. Throughout that period, various crises hit the world and Indonesia such as economic, social, and political crises. This research uses historical methods with the following stages; topic selection, heuristics, interpretation, data analysis, and historiography. The results showed that the Kebon Agung sugar factory was part of the history of the sugar industry in the colonial period which contributed to the increase in sugar production in the Dutch East Indies. This sugar factory was able to survive the crisis that accompanied its history because of its efficiency strategy, production reduction, and cooperation with other sugar factories in terms of utilizing pre-existing infrastructure such as no longer building railways and roads for the transportation of raw materials (sugarcane) to the factory. In the midst of the crisis and the threat of bankruptcy, the Kebon Agung Sugar Factory still survived and continued to carry out production activities until the sugar factory was nationalized in 1958. Thus, the Kebun Agung Sugar Factory also recorded its history by contributing to efforts improve the state economy.